3D Bioprinting of Lignocellulosic Biomaterials. Issue 24 (26th October 2020) - Shavandi, Amin; Hosseini, Soraya; Okoro, Oseweuba Valentine; Nie, Lei; Eghbali Babadi, Farahnaz; Melchels, Ferry
Abstract: The interest in bioprinting of sustainable biomaterials is rapidly growing, and lignocellulosic biomaterials have a unique role in this development. Lignocellulosic materials are biocompatible and possess tunable mechanical properties, and therefore promising for use in the field of 3D‐printed biomaterials. This review aims to spotlight the recent progress on the application of different lignocellulosic materials (cellulose, hemicellulose, and lignin) from various sources (wood, bacteria, and fungi) in different forms (including nanocrystals and nanofibers in 3D bioprinting). Their crystallinity, leading to water insolubility and the presence of suspended nanostructures, makes these polymers stand out among hydrogel‐forming biomaterials. These unique structures give rise to favorable properties such as high ink viscosity and strength and toughness of the final hydrogel, even when used at low concentrations. In this review, the application of lignocellulosic polymers with other components in inks is reported for 3D bioprinting and identified supercritical CO2 as a potential sterilization method for 3D‐printed cellulosic materials. This review also focuses on the areas of potential development by highlighting the opportunities and unmet challenges such as the need for standardization of the production, biocompatibility, and biodegradability of the cellulosic materials that underscore the direction of future research into the 3D biofabrication of cellulose‐based biomaterials. Abstract : Lignocellulosic biomaterials are nanostructured polymer materials that possess unique properties, making them promising for use in 3D bioprinting. This article reviews recent progress in the application of different lignocellulosic materials (cellulose, hemicellulose, and lignin) from various sources in the field of 3D bioprinting.